2017
DOI: 10.1155/2017/4654958
|View full text |Cite
|
Sign up to set email alerts
|

Design, Development, and Optimization of Dexibuprofen Microemulsion Based Transdermal Reservoir Patches for Controlled Drug Delivery

Abstract: The aim of the study was to develop a reservoir-type transdermal patch for a controlled delivery of dexibuprofen and to evaluate its in vivo anti-inflammatory activity in Albino Wistar rats. In order to develop these patches, six formulations of dexibuprofen microemulsion comprising ethyl oleate, Tween 80: PG (2 : 1), and water were prepared by simplex lattice design and characterized. The reservoir compartment was filled with these microemulsions and in vitro release and skin permeation were assessed. The opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…All the formulations best comply with Makoid-Banakar model showing R 2 values in the range of 0.998-0.999 as shown in Table 3. The reservoir patches of estradiol [22] and dexibuprofen [41]. have also followed the Makoid-Banakar model.…”
Section: In Vitro Release Studymentioning
confidence: 99%
See 1 more Smart Citation
“…All the formulations best comply with Makoid-Banakar model showing R 2 values in the range of 0.998-0.999 as shown in Table 3. The reservoir patches of estradiol [22] and dexibuprofen [41]. have also followed the Makoid-Banakar model.…”
Section: In Vitro Release Studymentioning
confidence: 99%
“…Thacharodi et al also concluded that the surface area of device affect the drug release and decrease in the area has also reduced the release of drug from the device [53] Fig 4(C) represents drug permeation from LRX patches with different surface area and was found approximately similar i.e 115.58 μg/cm 2 /h, 110 μg/cm 2 /h and 126.51 μg/cm 2 /h, respectively Similar findings were reported by Ali et al, where a change in the surface area resulted in a different release profile but approximately similar permeation profile. [41].…”
Section: Effect Of Gelling Agent Concentrationmentioning
confidence: 99%
“…Dexibuprofen, a NSAID has been reported to possess several biological activities such as anti-inflammatory, reported that the reservoir-type transdermal patch exhibiting controlled zero-order rate of release with suitable permeation rate was prepared. The findings of in vitro studies suggest effective delivery of dexibuprofen across skin 30 . Gels were prepared by dispersing the polymers in a mixture of water and glycerol with methyl paraben as the preservative and the varying amount of ibuprofen, being kept under magnetic stirring until the homogeneous dispersion was formed.…”
Section: Discussionmentioning
confidence: 95%
“…Other authors have also developed DXI transdermal patches for controlled DXI delivery [ 70 ]. In this sense, Ramzan Ali and colleagues developed a reservoir-type transdermal patch for a controlled delivery of DXI and evaluated its in vivo anti-inflammatory activity performing the carrageenan hind paw edema test in Albino Wistar rats.…”
Section: Novel Strategies For Dexibuprofen Drug Deliverymentioning
confidence: 99%
“…The formulation patch was compared with commercial DXI (previously dissolved tablets) in vivo, obtaining a plasmatic concentration 1.9 times higher with DXI patches than with the oral tablets [69]. Other authors have also developed DXI transdermal patches for controlled DXI delivery [70]. In this sense, Ramzan Ali and colleagues developed a reservoir-type transdermal patch for a controlled delivery of DXI and evaluated its in vivo anti-inflammatory activity performing the carrageenan hind paw edema test in Albino Wistar rats.…”
Section: Novel Strategies For Skin Dexibuprofen Deliverymentioning
confidence: 99%